2017
DOI: 10.1177/1757913917737563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a museum-based social prescription intervention on quantitative measures of psychological wellbeing in older adults

Abstract: Social prescribing interventions have ranged from physical exercise (e.g. exercise referral, green gyms) to personal study (e.g. books on prescription, education on prescription) and creative activities (e.g. arts on prescription including dance, film, music and painting). Schemes that have sought to address the social determinants of health include information prescriptions (e.g. debt advice, housing, welfare); healthy living initiatives (e.g. smoking cessation, healthy eating, health checks); social enterpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
136
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(171 citation statements)
references
References 30 publications
(46 reference statements)
5
136
0
1
Order By: Relevance
“…29,30 The creative methods of art and medical humanities are also needed to investigate how different forms of material engagement achieve their effects. [31][32][33] Some of the key issues include: (a) the role of arts and creative industries in psychotherapy; 33,34 (b) the development of evidence-based understandings of the therapeutic effects and qualities of different art materials and digital media; (c) the role of museums in mental health [35][36][37][38] as a space for creative interventions; and (d) the cross-cultural, 39 social and gender 40 dimensions of mental health.…”
Section: The Materials Engagement Approachmentioning
confidence: 99%
“…29,30 The creative methods of art and medical humanities are also needed to investigate how different forms of material engagement achieve their effects. [31][32][33] Some of the key issues include: (a) the role of arts and creative industries in psychotherapy; 33,34 (b) the development of evidence-based understandings of the therapeutic effects and qualities of different art materials and digital media; (c) the role of museums in mental health [35][36][37][38] as a space for creative interventions; and (d) the cross-cultural, 39 social and gender 40 dimensions of mental health.…”
Section: The Materials Engagement Approachmentioning
confidence: 99%
“…For instance, a randomised controlled trial on participatory singing activities reported its effectiveness in enhancing quality of life, and reducing anxiety and depression among older intervention participants 12. Moreover, the Museums on Prescription Study showed that cultural heritage engagements were effective in improving psychological and social well-being 13 14. Moreover, the efficacy of the arts in the treatment of mental health conditions, as well as support for the treatment of various chronic health conditions were well documented 15 16.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that participatory art-based activities may improve aspects of mental health such as positive emotions and self-esteem [3][4][5][6]. Art-based activities help patients, regardless of their disease, to build a sense of self, transforming the illness experience into a positive experience and improving patients' well-being and quality of life [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Well-being, defined as a good or satisfactory condition of existence, quality of life, and health are closely related, and this relationship is important at older ages [9,10]. Wellbeing is positively associated with quality of life and physical health benefits, including a decreased risk for disease, speedier disease recovery, and increased longevity [6][7][8][9][10][11][12][13]. In parallel, it has been found that art-based activities are positively associated with numerous aspects of individuals' physical health, like a better immune system response and slower disease progression, with these effects being related to well-being improvement [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%